(3HZjI GdeQjO hCfS GdaQjO ajef hdOg GdSjO Ydi Hf eMeO Hf Ydi Hf GdQTjOs - (3YGeQ Hf eMeO Hf YHO Gddg Hf YGeQ Hf Ydj Hf eMeO Hf Ydj Hf GdQTjOs ((3GdbGSe Hf YHO GdeDef Hf GdMSf Hf Ydi Hf GdeJhcd Edi Gddg s)
(3ChdgG (B:s
(3GdMeO ddg GdPi gh Ydi JZGjQ GdCRefI Edg eMehO s
(3BNQgG (B:s
(3age eTGjN GdYdhe heQLY GdMdhe , hEdjge jQLY YfO GdegeGJ , hJSJfRd Hge GdNjQGJ hGdHQcGJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3ai JQGLe GdSGOI GdgOhjjfs
(3Ydi MhGTi GdfSNI TQhM cKjQI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs